Mastication and swallowing: influence of fluid addition to foods - Luciano José Pereira; Maria Beatriz Duarte Gavião; Lina Engelen; Andries Van der Bilt (University of São Paulo, 2007)
INTRODUCTION: The production of sufficient saliva is indispensable for good chewing. Recent research has demonstrated that salivary flow rate has little influence on the swallowing threshold. OBJECTIVES: The hypothesis examined in the present study was that adding fluids to foods will influence chewing physiology. Materials and METHODS: Twenty subjects chewed on melba toast, cake, carrot, peanut and Gouda cheese. They also chewed on these foods after addition of different volumes of water or alpha-amylase solution. Jaw muscle activity, number of chewing cycles until swallowing and chewing cycle duration were measured. Repeated measures analysis of variance was applied to test the null hypothesis that there would be no statistically significant difference among the results obtained for the various food types and fluids. Subsequently, contrasts were determined to study the levels of intra-subjects factors (food type and fluid volume). Linear regression was used to determine the changes in muscle activity and cycle duration as a function of the chewing cycles. RESULTS: Fluid addition significantly decreased muscle activity and swallowing threshold for melba, cake and peanut (p<0.05). The effect of alpha-amylase in the solutions was similar to that of water (p>0.05). Doubling the volume of tap water had a greater effect. CONCLUSIONS: Fluid addition facilitated chewing of dry foods (melba, cake), but did not influence the chewing of fatty (cheese) and wet products (carrot). This study is relevant to improve patients' life quality and the management of chewing and feeding disorders caused by hyposalivation.